Synthetic and physical organic studies of chromone derivatives - Ramaite, Ipfani David Isaiah (Rhodes University, Faculty of Science, Department of Chemistry, 1997)
A range of chromone-2-carboxylic acids has been prepared by condensing suitably substituted 2-hydroxyacetophenones with diethyl oxalate. pK₂ Studies of these acids revealed that 6- or 7-methoxy substituents decreased acidity while the 6-nitro group enhanced acidity; the strongest acid was the 3-chloro derivative, the increase in acidity being attributed to steric inhibition of acid-weakening delocalisation between the carboxyl group and the chromone system. Various chromone-2-carboxamides, derived from acid chloride precursors, were converted to polysubstituted acrylamides by nucleophilic ring-opening with selected amine nucleophiles. The main fragmentation patterns exhibited by these acrylamides were elucidated using a combination of low resolution, high resolution and meta-stable peak analysis, while the effect of substituents on the simultaneous internal rotation involving the carboxamide and enamine moieties were studied using dynamic NMR spectroscopy. Rotational barriers of ca. 67.1 kJmol ̄¹ and ca. 102 kJmol ̄¹ were found for the enamine and amide rotors, respectively. Several synthetic pathways were followed to prepare a series of 2-(N,N-dialkylamino)chromones which were subjected to detailed mass spectral analysis. In addition to substituent-specific fragmentations , the 2-aminochromones appear to fragment via 3 major pathways. The effect of substituents on the internal rotation of the amino moeity was investigated by variable temperature ¹H NMR spectroscopy and the resulting DNMR data was used to calculate the rotational barriers. Examination of the data reveals that the electron-releasing 6- and 7- substituents reduce the C-NMe₂ rotational barrier to ca. 43.5 kJmol ̄¹ , while the nitro analogue has the largest rotational barrier (ca. 46.1 kJmol ̄¹) because of the electron-withdrawing effect of this substituent.
Keywords: Benzopyrans; Heterocyclic compounds -- Derivatives; Coumarins